Moral Literacy and Islamic Values among Students at Tertiary Level - Muhammad Shoaib; Behzad Anwar; Raza Mustafa (الآفاق اسلامی و تحقیقی مجلہ, 2022)
The present study has been designed to analyses moral literacy and Islamic values among students in higher education institutions (HEIs) in Pakistan. Moral literacy and Islamic values are taught in all educational institutions in Pakistan directly and indirectly. A sample of 1512 university students of the BS program (4 Years) has been selected through a proportionate random sampling technique from two faculties of the University of Gujrat i.e. Faculty of Arts and Faculty of Social Sciences. A cross-sectional survey has been conducted using a structured questionnaire from the students. Pilot testing has been conducted on 30 randomly selected students to proceed to the final data collection. The study findings show that moral literacy and social justice have a favorable effect on the teaching of Islamic values to students at the tertiary level of education. It is worth stating that the study also shows a similar nature of results in favour of forgiveness and kindness to predict Islamic values. It is believed that faith plays an important role in the promotion of social justice, forgiveness, kindness, humanity respect, sincerity, and moral literacy in Pakistan.